Effects of Background Variables of Early Childhood Teachers on Their Concerns About Inclusion: The Mediation Role of Confidence in Teaching. Issue 2 (3rd April 2018) - Park, Mi-Hwa; Dimitrov, Dimiter M.; Park, Do-Yong
ABSTRACT: This study examines concerns of early childhood teachers about inclusive education (IE) in infant through 3rd-grade classrooms in the United States and the associated role of teachers' background variables. The data consisted of the responses of 679 early childhood teachers on a survey about their concerns. The data analysis supported the presence of four correlated latent factors of concerns related to difficulties about IE, work load with IE teaching, appropriateness of IE, and school resources for IE. The effects of teachers' background variables on each factor of concerns about IE were examined in the framework of structural equation modeling. The results revealed that the effects of teachers' training on teaching children with disabilities, teaching experience with children with disabilities, and having a family member (or a close friend) with a disability on their concerns about IE are mediated by their confidence in teaching children with disabilities. The results suggest that improving early childhood teachers' confidence for effective inclusive education is coming to the forefront of teacher training.